Hermite-Hadamard and Simpson-Like Type Inequalities for Differentiable (𝛼,𝑚)-Convex Mappings - Jaekeun Park (International Journal of Mathematics and Mathematical Sciences)
The author establish several Hermite-Hadamard and Simpson-like type inequalities for mappings whose first derivative in absolute value aroused to the 𝑞th (𝑞≥1) power are (𝛼,𝑚)-convex. Some applications to special means of positive real numbers are also given.